THE BIG FIVE PERSONALITY TRAITS TERHADAP FINANCIAL LITERACY DAN INVESTOR RISK BEHAVIOR PADA KELOMPOK INVESTOR GENERASI Z - Putri, Safira Ananda; Ferli, Ossi (Journal of Accounting, Management and Islamic Economics, 2024)
This research aims to determine the influence of The Big Five Personality Traits on Financial Literacy and Investor Risk Behavior among Generation Z investors. The hypothesis testing in this research utilizes the PLS (Partial Least Square) method using SmartPLS 4.0. Data collection techniques involve using a Google Form questionnaire to gather the required information. The sample in this study consists of 165 Generation Z individuals participating in investments in the Indonesian Capital Market. The analysis results show that the Personality Trait (Neuroticism) has a positive and significant effect on Investor Risk Behavior, and there are 4 Personality Trait indicators that do not have a positive effect on Investor Risk Behavior, namely Agreeableness, Extraversion, Conscientiousness, and Openness to Experience. The Personality Trait (Openness to Experience) has a positive and significant effect on Financial Literacy, and there are 4 Personality Trait indicators that do not have a positive effect on Financial Literacy, namely Agreeableness, Neuroticism, Conscientiousness, and Extraversion. Financial Literacy has a positive effect on Investor Risk Behavior. Higher education can play an important role in improving financial and investment literacy among Generation Z.